DETERMINE THE SUCCESS OF NEIGHBORHOOD PARK: TAMAN TASIK LIPUR KOTA MUADZAM SHAH, PAHANG, MALAYSIA - Hanisah binti Othman; Nur Shafinda Wani binti Shaikh Azmee; Maisarah binti Awang (CV. RADJA PUBLIKA, 2025)
A good park gives a lot of benefits to the community. There are 3 main benefits of public parks, such as economic, environment and social. The public park is managed by the Local Authorities of the area. This study aimed to examine the successful of neighborhood park Taman Tasik Lipur Kota Muadzam Shah, Pahang. The study area is Taman Tasik Lipur Kota, Muadzam Shah, Pahang. The respondents involved are 125 respondents, it was the communities that visited the area during their leisure time. The method adopted in these studies included procedures using quantitative variables and measures such as Likert scale. Overall, the findings show that the mean of Good Accessibility and Linkages (GAL) is 3.30, Comfort and Image (DCI) is 3.26, User and Activities (UAC) is 3.87 and Sociability (SOC) is 3.86. The result found the Taman Tasik Lipur kota Muadzam Shah still needs improvement in terms of Accessibilities and linkages, comfort and image, user and activities and sociability. However, the number of visitors to the park is high during weekends and evenings. In conclusion, this study recommends that the park should increase the safety of the park. The behavior of the visitor during their visit of the park such as bringing the car and the motorbikes inside the park make the other visitor feel insecure. On the other hand, the government also can increase the public transportation and Bus Stop to increase the number of visitor of the park. The local government can encourage in term of Good Accessibility and linkages (GAL) and Comfort and Image (DCI) of Taman Lipur Kota Muadzam Shah, Pahang.